Journal of Transport Economics and Policy (JSTOR)
The Journal of Transport, Economics and Policy (JTEP) was first published 40 years ago and quickly established itself as an essential source of information and debate on the economics of transport and its interface with transport policy
Keywords: Business, Business & Economics, Economics, Social Sciences, Transportation Studies